104. Assessment of distal compound muscle action potential duration (DCMAPD) in paediatric chronic inflammatory demyelinating polyneuropathy (CIDP). Issue 1 (January 2015) - Rossi, D.P.; Fornarino, S.; Pedemonte, M.; Lamba, L. Doria; Lanteri, P.
<x xml:space="preserve">Abstract</x> To evaluate if duration of distal compound muscle action potential duration (DCMAPD) could represent a sensitive parameter in clinical practice to add to established electrophysiological diagnostic criteria in paediatric chronic inflammatory demyelinating polyneuropathy (CIDP) and its rule in patient's follow-up. We retrospectively reviewed records of 8 children affected by CIDP (6/8 possible CIDP, 2/8 confirmed CIDP) according to established diagnostic criteria of the 88th ENMC International Workshop (2000), before consideration of DCMAPD prolongation. Patients were studied with EMG equipment with low-cut filter settings ⩽10 Hz. Using adult cut-offs to define DCMAPD prolongation it was present in 8/8 patients for peroneal nerve, in 6/8 for median nerve and in all five patients in which we recorded tibial nerve. During follow-up time clinical worsening corresponded always to a greater DCMAPD prolongation compared with other electrophysiological parameters (amplitude, distal latency and nerve conduction velocity). Appropriate evaluation of DCMAPD appears an essential criterion to consider in assessing suspected CIDP and to support clinical worsening in follow-up, which may be helpful in limiting extensiveness and duration of electrophysiological testing, thereby reducing patient discomfort, especially in children.